Criminal exploitation in northern Chile: The case of foreign women acting as “human couriers” for drug trafficking (Delito y Sociedad, 2025)
This article analyzes the relationship between the involvement of foreign women in cross-border drug trafficking and human trafficking for criminal exploitation. In particular, it explores cases in which the crime of drug trafficking is a consequence of exploitative practices typical of human trafficking, such as abuse of a situation of vulnerability, deception or coercion. From there, the article studies the dynamics that occur in the criminal justice system when the status of trafficker (of drugs) and victim (of trafficking) overlap. The research focused on the northern regions of Chile (Arica and Parinacota, Tarapacá and Antofagasta) and was carried out using a qualitative methodology that included semi-structured interviews with women deprived of liberty for drug trafficking and operators of the penal system as a data collection technique. The results suggest that trafficking in persons for criminal exploitation is an emerging phenomenon in Chile that tends to be made invisible by the dynamics that revolve around how drug trafficking is processed.
Keywords: criminal exploitation; incarcerated women; human couriers; drugs trafficking; non-punishment principle